O. V. Ivasiuk : THE TERM GNEZDO AS A SYSTEMAZING UNIT OF THE LINGUISTIC METALANGUAGE - Ivasiuk, О.V. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Introduction. The article is devoted to the topical issue of the formation and functioning of the linguistic terminology system, in particular, terms including the word “gnezdo” as a basic word. Most of them are composite, and the main information load is presented in their attributive part, which indicates either the object of the description or the approach to its description. Purpose. The purpose of the article is to identify the conceptual content of terms including the basic component gnezdo (word-family) and their coordination in the metalanguage of linguistics. Results. Due to the multivector nature of scientific paradigms in linguistics of the XXI century there is a question of the continuity of the terminological toolkit and the issues arisen in this regard. In particular, derivatologists-cognitivists, considering a word-family, proceed from natural-logical prototypical connections that are significant for linguistic consciousness, and model a propositional-frame structure of the interaction of one-root words. They proceed from the fact that such a word-family as integrity is based on the referential correlation of the same-root units, however, terms “derivational word-family”, “derivative word-family” in relation to a group of words united on the basis of only motivational relations without taking into account derivative relations are widely used. It is more expedient to call such paradigms “cognate word-family” (single-root word-family (not to be confused with root word-family), since a derivational word-family is built taking into account word-building rather than lexical motivation and is structured taking into account derivational steps and the derivational structure of the derivative. Due to the conceptual content difference of the terms considered, it is necessary to follow the accuracy of their use: in cognitive derivatology, the term “cognate word-family” is used, and in traditional derivatology, the term “derivational word-family” to denote the largest structural complex unit of wordbuilding.The terms used in synchronic and diachronic derivatology (“cognate word-family” vs “root word-family”) require strict differentiation.Originality. Along with the regular compound terms including component gnezdo, the conceptual content of the new term “divergent word-family” is analyzed in derivatology for the first time. Conclusions. In classical derivatology, over the past decades, a research gap has been filled, which resulted in the allocation of word-families of a special type, which led to the emergence of new terms – “explanatory-derivational word-family, or lexical-derivational word-family” and “divergent word-family”. These terms are applicable to word-families with a polysemic top-word. In the first type of word-families, it is taken into account from which lexical-semantic variant of the generative the derivative is formed, in the second – in which of its LSV the derivative is presented, therefore this type of a word-family is formed in mutual projection with the epigmatic word-family of the common word for them (it is formed due to semantic derivation), forming a derivational word-family, or a derivational space of a lexeme.